2009
DOI: 10.1556/abiol.60.2009.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prometryne on subchronically treated mice evaluated by SCGE assay

Abstract: Prometryne is a methylthio-s-triazine herbicide used to control annual broadleaf and grass weeds in many cultivated plants. Significant traces are documented in environment, mainly water, soil and plants used for human and domestic animal nutrition. Data on the toxic effects of prometryne and other methylthio-s-triazine have scorcely been published. The goal of this study was to investigate if prometryne, applied orally, could induce DNA damage in mouse leukocytes, in subchronical in vivo experimental design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The only records available in literature refer to the neurotoxic kinetics of atrazine, a pesticide structurally similar to prometryne (23,24,26). Due to similar structure, the two compounds may share some toxicological properties (33,34). Our results confi rm this assumption, as they correspond to the fi ndings of Stoker and Cooper (40), who examined the toxicokinetics of atrazine in rat brain and other organs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The only records available in literature refer to the neurotoxic kinetics of atrazine, a pesticide structurally similar to prometryne (23,24,26). Due to similar structure, the two compounds may share some toxicological properties (33,34). Our results confi rm this assumption, as they correspond to the fi ndings of Stoker and Cooper (40), who examined the toxicokinetics of atrazine in rat brain and other organs.…”
Section: Discussionsupporting
confidence: 85%
“…One of the goals was to compare the allometric differences (30)(31)(32) between rats used in the study of Maynard et al (22) and mice which we regularly used in earlier prometryne toxicity studies (33,34). One of the key documents that directed the experiment was the OECD 407 guideline for 28-day subchronic toxicity studies in rodents (21).…”
Section: Discussionmentioning
confidence: 99%
“…Since prometryn is widely used across the world as an herbicide to control the growth of annual broadleaf and weeds in many cultivated plants, there are possible cases that humans are at risk of being exposed to prometryn and other commonly used pesticides more than expected. Prometryn is relatively persistent in waters, soil, and even air near application sites [29]. Significant traces of prometryn have been documented to be remnant in plants used for human and domestic animal consumption [30,31] and some medicinal plants that were protected with prometryn [32].…”
Section: Discussionmentioning
confidence: 99%
“…They reported a significant increase in comet TL in atrazine-exposed animals compared to controls, in blood and liver cells. In a study of prometryn on mice exposed to three doses for 28 days, Đikić et al [63] found dose-and exposure-related DNA damage in the leukocytes.…”
Section: Discussionmentioning
confidence: 99%